Living with celiac disease in Kazakhstan: a qualitative study - Kaniyev, Daniyar (Nazarbayev University School of Medicine, 2019)
Celiac disease represents a problem to Kazakhstani population not only because of its growing prevalence in children, clinical manifestations and possible health complications. Another issue celiac disease poses to society is a diminished quality of life in patients and their families. This study aims to explore what people with celiac disease are going through, and what are the main obstacles to maintain a gluten-free diet...
Keywords: celiac disease